Pengaruh Pemberian Layanan Informasi Tentang Self Personality Terhadap Konsep Diri Siswa Di Smp Negeri 2 Merapi Barat - Anisyah Juniarti; Edi Harapan; Ramtia Darma Putri (Departement of Mathematics Education, 2024)
Self-concept is a picture or view of self that is owned by each individual both physical, psychological, and social-emotional characteristics. Without the formation of a good and appropriate self-concept, it will cause difficulties for individuals to understand themselves. This study aims to determine the effect of information services about self personality on students' self-concept at SMP Negeri 2 Merapi Barat. This study used a quantitative method with an experimental design, One Group Pre-test and Post-test. The population in this study were 145 class VIII students at SMP Negeri 2 Merapi Barat. The sample consisted of 28 students who were determined using a purposive sampling technique. Data collection techniques in this study used the Wilcoxon Test. Instrument validity was carried out in 2 (two) ways, namely construct validity and content validity. Instrument reliability uses the Split Half formula. Test the hypothesis using the Wilcoxon test. The results showed that the tcount was 0.000 and the ttable value was 0.05 with a significance level of 5%. Thus, tcount > ttable, then there are significant differences in students' self-concept before and after being given information services about self personality.Keywords: Self Concept, Information Services, Self Personality